End-users' perception of energy efficiency at healthcare facilities: a case study of Batu Gajah Hospital, Perak / Jamaludin Muhamad ... [et al.] - Muhamad, Jamaludin; Ismail, Amirul Amin; Mohamed Noor, Nur Azdli; Md Yusof, Md Anwar (2022)
The demand for energy efficiency has risen due to the depletion of non-renewable energy sources and greenhouse gas emissions. Energy efficiency aims to reduce energy consumption to perform the same tasks as the conventional method, including building operations. Hospital and healthcare facilities are known to be energy-intensive buildings. The ever-increasing demand for energy efficiency in hospital buildings has been recognised as smart economic management and countermeasure thus will provide better care for the public. High dependence solely on the mechanical system is not sustainable in the long run and various studies have established the optimal corrective measures of hospital design by combining passive and active systems to achieve optimal energy saving. This paper examines the end user's perception of the hospital's energy consumption in the Hospital Batu Gajah, Perak ward area. The study was conducted by using questionnaire administration and due to the nature of the healthcare setting the anonymity of inpatient ward users is preserved. Response by the end-users plays a massive role in addressing the efficiency of energy use in hospital and healthcare settings. The outcome of this paper will benefit the designers for a systematic guideline and consideration for hospital design, ultimately improving the efficiency of energy consumption for hospitals.